Antimutagenic activity of the Siberian herbs - S. N. Yefimov; S. I. Dmitruk; N. N. Ilyinskikh (Бюллетень сибирской медицины)
The antimutagenic activity of 41 Siberian herbs has been studied with microcores analysis method (calculation of micronucleous erythrocyte number in peripheral blood of mice). The most active species have been composed in herb preparations and the preparation with the most activity has been revealed with microcores analysis method. The microcore number decrease has been observed up to 1,80‰. Antimutagenic herb preparation activity is defined by the content of vitamins, pigments, coumarins, polyphenol complex, flavonoids, terpenic saponins, lactones and other compounds.